EVALUASI PROGRAM PELAKSANAAN KEGIATAN MASA PENGENALAN LINGKUNGAN SEKOLAH (MPLS) MENGGUNAKAN MODEL CIPP DI SMP NEGERI 11 KUPANG : Evaluasi program MPLS menggunakan model CIPP - Ninda, Ninda Kee; Riada Barang, Tius; Lakapu, Stenli; Nuban, Robi (Manajer Pendididikan, 2025)
This study aims to evaluate the implementation of the School Orientation Program (MPLS) at SMP Negeri 11 Kupang using the CIPP evaluation model (Context, Input, Process, Product). The method used is qualitative with an evaluative study type. The research subjects include the Vice Principal for Student Affairs and the Head of the MPLS Committee. The evaluation results show that: (1) contextually, the program aligns with school policy and needs; (2) in terms of input, sufficient resources are provided; (3) the process is systematic and well-organized; (4) the product shows all 320 admitted students successfully participated in the MPLS program